Navigating Colonialism through Sports - Ribeiro, Orquídea (2022)
“Navigating colonialism through Sports in Portuguese Africa” aims to present a brief review of literature on the importance of sports in the African colonies/provinces of the Portuguese Colonial Empire, namely regarding the diffusion and the appropriation of sports – as a tool of colonial control and repression by the coloniser and as a tool of resistance by the colonised. The research question focuses on the fact that the colonised accepted (European) sports but also used the opportunity to resist the colonial system. The selected articles reflect on the role of colonialism and its link to the effort placed on the use of sports to promote national cohesion and identity building (coloniser) or to promote resistance (colonised). The different studies prove that football/soccer was the most practised sport in the former colonies during the Portuguese occupation.